Characteristics of polyaniline nanoparticles prepared by electrochemical solution plasma process for flexible devices. Issue 1 (21st June 2022) - Jung, Eun Young; Park, Choon-Sang; Shin, Jun-Goo; Jang, Hyo Jun; Bae, Gyu Tae; Shin, Bhum Jae; Tae, Heung-Sik
Abstract: This paper systematically investigates the characteristics of polyaniline (PANI) nanoparticles (NPs) synthesized by an electrochemical solution plasma process (SPP) method in terms of various case studies such as gas flow rates, synthesis times, and post-heating temperatures. The FE-SEM and XRD results show that PANI NPs have spherical particles with a nanoscale and crystalline phases of PANI NPs show amorphous nature with the (020) and (200) crystallographic planes. In FT-IR and XPS spectra, several peaks are observed in PANI NPs powders, which are related to carbon-containing groups and nitrogen-containing groups due to PANI polymer units.